Morning and evening exercise - Dae Yun Seo; SungRyul Lee; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Byung Joo Park; Jin Han (Integrative Medicine Research)
A growing body of evidence suggests that exercise may contribute to preventing pathological changes, treating multiple chronic diseases, and reducing mortality and morbidity ratios. Scientific evidence moreover shows that exercise plays a key role in improving health-related physical fitness components and hormone function. Regular exercise training is one of the few strategies that has been strictly adapted in healthy individuals and in athletes. However, time-dependent exercise has different outcomes, based on the exercise type, duration, and hormone adaptation. In the present review, we therefore briefly describe the type, duration, and adaptation of exercise performed in the morning and evening. In addition, we discuss the clinical considerations and indications for exercise training.